Development of concentrating dish and solar still assembly for sea water desalination. (2021) - Abubakkar, A.; Selvakumar, P.; Rajagopal, T.; Tamilvanan, A.
Abstract: The availability of fresh water is approximately 1% and the availability of sea water is nearly 99%. The freshwater is depleting rapidly as the demand of it increases year by year. In order to solve this, desalination of sea water is the only solution. Desalination which is in practice in many parts of the world are typically based on the need of large amount of high grade energy. To have a sustainable development, the desalination should be carried out by means of available renewable energy. In this paper a small scale desalination system is designed. In this system, a parabolic dish is used to concentrate the radiation coming from the sun to the focal point and a solar still is placed at the focal point. The pH, hardness, chloride and TDS were determined before and after the conduct of experiment. The evaporation and condensation process inside the still gives water with a lower TDS.